A preliminary faunistic study of soil nematodes from different land uses in Tropical Deciduous Forest in the Costa Chica of Guerrero, Mexico - Garibay-Arciniega, Joselin; Mundo-Ocampo, Manuel; Rosas-Acevedo, José Luis; Guzmán-Martínez, María; Sampedro-Rosas, María Laura; Violante-González, Juan; De Ley, Paul (Instituto de Ecología, A.C., 2022)
Tropical Deciduous Forest (TDF) is an important biome threatened globally by climate change and human encroachment. Changes in diversity and abundance of soil nematodes can serve as indicators of soil disturbance due to human activities. Our objective was to present a first inventory of the generic biodiversity of soil nematodes in seven TDF sites subjected to different current or decade-old land uses, located near Copala in the Costa Chica region of Guerrero, Mexico. TDF landscapes are especially heterogeneous in many soil and microclimate parameters, while subsistence agriculture systems in this biome are highly diverse and present great challenges for sampling design with replication. We therefore chose to focus on characterizing the soil nematode fauna, as a first step before undertaking detailed analyses of all potentially relevant biotic and abiotic factors. Genus-level diversity ranged from 12 to 18 taxa for the sampled land uses, or 27 total taxa for all samples combined. Statistical tests for data analysis without replication revealed significant differences in nematode diversity, trophic structure, and abundance between land uses. Four sites, left as fallows for ten years after prior human uses, were statistically different from each other as well as from a forest site undisturbed for at least twenty years. Despite the methodological limitations inherent in this initial study, we hypothesize that some effects on nematode communities may persist for more than a decade after the anthropogenic impacts of subsistence farming in TDF. Thus, future nematode surveys in the TDF biome should not only analyze the current properties of sampling sites, but also document data related to factors from past human use activities. Example factors, suggested by the pattern of nematode abundance from the seven sites in our study, include past levels of trampling by human traffic and grazing, as well as estimates of past amounts of plant debris deposition accumulated by harvesting or weeding.